Giant Protruding Nodular Fasciitis of the Anterior Chest Wall Clinically Mimicking a Soft Tissue Sarcoma. (3rd July 2019) - Kinoshita, Hideyuki; Yonemoto, Tsukasa; Kamoda, Hiroto; Hagiwara, Yoko; Tsukanishi, Toshinori; Orita, Sumihisa; Inage, Kazuhide; Hirosawa, Naoya; Ohtori, Seiji; Ishii, Takeshi
Abstract : Nodular fasciitis (NF) is a benign reactive proliferation of myofibroblasts that predominantly occurs subcutaneously. Commonly, it presents as a rapidly growing swelling in 4-8 weeks. NF mostly occurs in adults aged 20-50 years and usually has adiameter < 3 ‐ 4 cm . Giant NF with adiameter > 4 cm is rare. Owing to its rapidly growing nature, a precise clinical diagnosis is difficult; it is frequently misdiagnosed as an aggressive or malignant tumor. Herein, we present the case of a 15-year-old male who presented with a large protruding mass on the anterior chest wall. The tumor appeared clinically malignant as it was protruding and had doubled in size within a few weeks, reaching approximately8 × 6 cm . Furthermore, the tumor separated and fell off spontaneously due to its large size. As the remaining tumor continued to grow rapidly, surgery was performed. Following wide tumor resection, no recurrence, metastases, or other complications were noted 1 year postsurgery. NF was diagnosed after pathological evaluation, including immunohistochemical analysis, molecular genetic testing, and cytogenetic testing via fluorescence in situ hybridization analysis. Knowledge of the atypical clinical course and a combination of histopathological examinations are necessary to accurately diagnose NF.